205k views
4 votes
Solve each equation by substitution

y = 3x + 4
y = 6x + 1

Options

• (7, 1)
• (1, 7)
• (-2, 4)
• (1, -7)​

2 Answers

5 votes

Answer:

(1, 7)

Explanation:

y = 3x + 4

y = 6x + 1

6x + 1 = 3x + 4 ⇒ x = 1

y = 3(1) + 4 = 7

(1, 7)

User Guido Lodetti
by
4.8k points
1 vote

Answer:

(1, 7)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define systems

y = 3x + 4

y = 6x + 1

Step 2: Solve for x

  1. Substitute in y: 3x + 4 = 6x + 1
  2. Subtract 3x on both sides: 4 = 3x + 1
  3. Subtract 1 on both sides: 3 = 3x
  4. Divide 3 on both sides: 1 = x
  5. Rewrite: x = 1

Step 3: Solve for y

  1. Define original equation: y = 6x + 1
  2. Substitute in x: y = 6(1) + 1
  3. Multiply: y = 6 + 1
  4. Add: y = 7
User Eren Aygunes
by
4.8k points